Bank of England base rate (Henry Stewart Talks, 2025)
Bank of England base rate definition, Influence on UK interest rates, Role in monetary policy and inflation control, Transmission mechanism to wider economy, Risks of prolonged low or high base rates, Impact on asset prices, borrowing, government spending